Development of IoT-Based Smart Waste Management Systems for Organic and Non-Organic Waste in Smart Cities - Aurelya Kirani Afkarien; I Gede Puja Astawa; Faridatun Nadziroh (The Indonesian Journal of Computer Science, 2025)
Public awareness of the importance of separating organic and inorganic waste and waste management is minimal, so there is a lack of public knowledge to distinguish between organic and inorganic waste. In addition, the slow transportation of garbage from the Temporary Disposal Site (TPS) to the Final Disposal Site (TPA) with a slow garbage truck can cause accumulation, so height monitoring that can be accessed remotely is needed. Based on these problems, it is necessary to have Organic and Inorganic Waste Detection tools and Internet of Things (IoT)-based altitude monitoring using infrared, capacitive, and inductive proximity sensors to distinguish between the two types of waste. This tool also monitors garbage height using ultrasonic sensors and the Ublox Neo 6mv2 GPS Module connected to the NodemCU ESP32 microcontroller to determine the longitude and latitude location point values. The altitude information will be sent to the Google Firebase server using WiFi and displayed on the App created using the MIT App Inventor.